2013
DOI: 10.1021/jp403504n
|View full text |Cite
|
Sign up to set email alerts
|

β-Scission of Olefins on Acidic Zeolites: A Periodic PBE-D Study in H-ZSM-5

Abstract: Eight β-scission modes involving C 6 and C 8 olefin isomers are investigated using dispersion-corrected density functional theory (i.e., PBE-D) calculations. Potential energy surfaces are evaluated within an acidic H-ZSM-5 supercell containing a single, isolated active site. Minimum energy pathways are localized using the nudged elastic band method. The relative enthalpic barriers of β-scission steps can be described by the substitution order of the carbocationic carbon atom present in the reactant and transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 65 publications
5
58
1
Order By: Relevance
“…Using an enthalpy of adsorption of a C8 alkene of À160 kJ mol À1 , calculated using the method of Fogash et al [23], a true activation energy around 140 kJ mol À1 is calculated. This value is in reasonable agreement with a reported value of 153 kJ mol À1 obtained computationally by Mazar et al [54] for beta-scission of 3,3-dimethylhexoxide on H-ZSM-5.…”
Section: Evidence That Bimolecular Pathways Dominate At ''High'' Alkesupporting
confidence: 93%
See 1 more Smart Citation
“…Using an enthalpy of adsorption of a C8 alkene of À160 kJ mol À1 , calculated using the method of Fogash et al [23], a true activation energy around 140 kJ mol À1 is calculated. This value is in reasonable agreement with a reported value of 153 kJ mol À1 obtained computationally by Mazar et al [54] for beta-scission of 3,3-dimethylhexoxide on H-ZSM-5.…”
Section: Evidence That Bimolecular Pathways Dominate At ''High'' Alkesupporting
confidence: 93%
“…An argument had been put forth that 2,2,4-trimethylpentane is selectively formed from n-butane and cracks to eventually make two isobutane molecules [57]. In light of the findings of de Lucas et al [55] and an equilibrium content of 2,2,4-trimethylpentane at 600 K of only 1.5 mol% [54], this preferential pathway is not a likely scenario.…”
Section: Evidence That Bimolecular Pathways Dominate At ''High'' Alkementioning
confidence: 99%
“…Compared to the previous studies on olefin transformation [2,8,10,14,15,31,32], the temperature investigated in this work is in moderate range. The temperature dependence indicates that, under the high temperature, the bimolecular cracking will be insignificant and the monomolecular cracking becomes dominant.…”
Section: Negative Temperature Dependence Of Cracking Ratementioning
confidence: 99%
“…Besides, the 6 th and 10 th reactions involve the β-scission of tertiary carbenium ion, therefore their activation energies are smaller than those of the 3 rd and 7 th reactions [8,32]. The predicted product distribution is shown in Figure 4-7, in which the reaction rate constants were calculated from the Arrhenius equation using the parameters presented in Table 3.…”
Section: As Shown Inmentioning
confidence: 99%
“…In the literature, energy barriers for b-scission steps in zeolites were evaluated mainly from alkoxides, with values as high as 150-200 kJ mol À1 [108][109][110][111][112]. Earlier studies performed on small clusters (neglecting confinement effect) even concluded to barriers above 200 kJ mol À1 [62][63][64][105][106][107].…”
Section: Cracking Stepmentioning
confidence: 99%